Treatment patterns and steroid dose for adult minimal change disease relapses: A retrospective cohort study. - Takaya Ozeki; Masahiko Ando; Makoto Yamaguchi; Takayuki Katsuno; Sawako Kato; Yoshinari Yasuda; Naotake Tsuboi; Shoichi Maruyama (PLoS ONE)
Background In patients with adult minimal change disease (MCD), proteinuria relapse is a problem to solve. However, the optimal relapse treatment regimen remains unclear regarding steroid dose. We described the treatment pattern of adult MCD patients and evaluated the appropriate steroid dose for relapse treatment. Methods This retrospective multicenter cohort study included 192 patients with adult biopsy-proven MCD from 14 hospitals in Japan. The prescription pattern of immunosuppressive drugs in relapse was reviewed. To assess the association between steroid dose used for relapse and subsequent outcomes, data of patients with tapered prednisolone (PSL) dosage to <10 mg/day before the first relapse in whom the dose was subsequently increased to ≥10 mg/day were extracted and assigned to the High-PSL or Low-PSL groups, based on the median dose of 20 mg/day. Multivariate Cox proportional hazard model and propensity score analysis with multiple imputations were conducted to compare their clinical course. Results During a median observation period of 37.6 months, 186/192 (96.9%) patients achieved complete remission (CR) and 100 (52.1%) relapsed. The median urinary protein level at the first relapse was 3.12 g/gCr or g/day. The proportion of non-steroidal immunosuppressant use increased with relapses; cyclosporine was the most common. No significant differences were found in the second relapse, frequent relapses, or adverse events between High-PSL (n = 34) and Low-PSL (n = 36) groups. A multivariate Cox proportional hazard model revealed that the hazard ratios adjusted with propensity score for the second relapse were 0.94 (High-PSL vs. Low-PSL; 95% confidence interval, 0.42-2.10; P = 0.88) and 0.82 (PSL dose per 10 mg/day; 95% confidence interval, 0.58-1.16; P = 0.25). Conclusions Among patients in CR with PSL dose <10 mg/day, higher steroid dose (PSL >20 mg/day) was not associated with favorable outcomes after the first relapse as compared to lower dose (10-20 mg/day).